Long-Lasting Follow-Up with Low-Dose Steroid in an 18-Year-Old Male with Rosai–Dorfman Disease - Volkan Karakuş; Yelda Morgül Dere; Dilek Ersil Soysal (Case Reports in Medicine)
Rosai–Dorfman disease (RDD) is a rare and benign pathology of sinus histiocytosis of unknown etiology. Lymphadenopathy is the predominant clinical manifestation, but diverse organs can also be affected. Histological features involve S-100+ histiocytes with characteristic nuclear features within the enlarged sinusoids of the lymph nodes. The clinical course is unpredictable, but is often benign with spontaneous resolution of disease in most patients. We report a patient with bilateral massive enlargement of cervical, axillary, and inguinal lymph nodes, moderately enlarged spleen, and a weight loss of 15 kg. Excisional biopsy from the cervical lymph node showed that the dilated sinusoids were infiltrated by lymphocytes, plasma cells, and large histiocytes with CD 68 and S-100 protein positive. Due to the slow progression of the disease, oral prednisolone with a body weight of 1 mg/kg was started in March 2016. The steroid dosage has been adjusted many times during the clinical follow-up. After 33 months, steroid treatment resulted in partial shrinkage of lymph nodes, the spleen returned to its normal size, and the patient gained weight. After 38 months of follow-up, no systemic symptoms, sign, or extranodal involvement were detected, and the patient continued with low-dose steroid treatment.